Location, Relocation, Dislocation Learning Cultures or Cultures of Learning? - Paul Armstrong (Adult Education Research Conference, 2006)
Following a recent organizational relocation, the impact on the teaching and learning became evident. In analyzing the impact of change, the most useful way of understanding the change was to utilize the postmodern concepts of location and (dis)location, and to consider using anthropological research techniques to identify cultures of learning.
Keywords: Location; learning; culture; postmodern; anthropology